Seeking the Christian Tutelage: Agency and Culture in Chinese Immigrants' Conversion to Christianity - Ng, Kwai Hang (Sociology of religion, 2002)
This paper explores the social mechanism through which assimilation and ethnic identification can be conceptualized not as mutually exclusive, but instead as intimately involved. Based on an ethnographic study of a Chinese immigrant church, this study finds that aspects of Chinese culture, particularly its understanding of the self, its imageries of deities, as well as its emphasis on practical blessings, have shaped the content of the religion in such a way that Protestantism is transformed into a local faith in the process. The central argument of this paper is that in the process of converting to mainstream religions in the United States, immigrants come to learn the “American way” through a creative deployment of their own cultural categories, symbols, and practices. The notion of agency as the conceptual link allows researchers to see assimilation and ethnic identification as different aspects of the same process of immigrants' social reidentification.